The Role of Agent in Islamic Financing: A Critique - Burhan Ali Shah (Türkiye İslam İktisadı Dergisi)
This study explores the role of agent in the Islamic modes of financing in order to identify ambiguities/issues related with the role of agent in Murabaha, Salam, Istisna and Tijara. The research further discovers the view of the Shari’ah experts with respect to such ambiguities so that they can either be verified as Shari’ah issues or non- Shari’ah issues. The role of agent was examined using content analysis of the model documents used by Islamic banks followed by soliciting the views of the Shari’ah specialists through interviews. No Shari’ah issue was found in hiring the customer as agent by the bank in any Islamic modes or binding the agent to act as an “undisclosed agent”. Conversely, the supplier’s risk, was declared to be the obligation of the bank and transferring this risk to the agent was observed as a real issue from Shari’ah point of view in the practice of Murabaha. Similarly, the principal is not allowed to charge any penalty to the agent if he is working without negligence and in good faith. Shifting charges like transportation, storage, etc., to the agent is not correct. However, no Shari’ah issue was found in binding the agent to provide collateral/security, etc., to the bank. Nevertheless, no consensus was observed on binding the agent to provide corporate guarantee. This research appears to be a preliminary but important attempt of its nature examining the critical role of agent in Islamic modes of financing adding value to the body of knowledge in Islamic banking.